Pengaruh Literasi Keuangan Dan Kepercayaan Terhadap Minat Penggunaan Shopee Pay Later - Aurin, Rizkiza; Kusumastuti, Ratih (Fakultas Ekonomi Prodi Akuntansi, 2023)
In the 2022 digital literacy report, Shopee has become the number one choice for online shopping in Indonesia with a market share of approximately 3.37%. Technological breakthroughs like SPayLater have provided convenience and trust to consumers in financial transactions. This research aims to evaluate the relationship between financial literacy and the level of trust among students and their interest in using SPayLater services. The research method used is an associative research method that focuses on exploring the relationship between financial literacy, trust levels, and interest in using SPayLater. The primary data was collected through a questionnaire distributed via Google Form, with a total of 50 respondent samples. The research results indicate that financial literacy and trust levels have a positive and significant impact on the interest in using SPayLater, emphasizing the importance of financial literacy and trust in promoting the use of financial technology like SPayLater.